Purchase Decision of Life Insurance Policyholders: An Outlook - Rajeswari, K.; Kartheeswari, S. (Indian Journal of Marketing, 2012)
The insurance industry has been a booming sector, and companies are going overboard to get and retain customers. At present, there are 23 private insurance companies including Indian Private insurance companies and Indian private insurance companies with foreign partners in India. These companies are competing with the LIC to tap the immense insurance market potential of India. After the new economic reforms and global economic recession, the insurance companies have started to review their marketing strategies relating to assessing the customer’s financial needs and their other economic expectations, budget allocation, sales targets, staff training, adopting sophisticated technology, office automation in order to compete with their counterparts emerging in the scenario. This paper is an attempt to know the purchase decision of life insurance policyholders in the study area, which is situated in South Tamil Nadu. It is observed that among the policy holders with different age groups, the younger groups have positive attitude with insurance plans than elders. Although there has been a significant and rapid advancement in the area of customer management, there are many issues that need to be explored. Insurance companies across the world have started recognizing the value of superior customer care.